High-performance liquid chromatographic determination of cotinine in urine in isocratic mode - Ceppa, Franck; El Jahiri, Younes; Mayaudon, Hervé; Dupuy, Olivier; Burnat, Pascal (Journal of chromatography. B, Biomedical applications, 2000)
A simple procedure for the determination of cotinine, major metabolite of nicotine in urine, is described. The assay involved a liquid–liquid extraction with dichloromethane in alkaline environment. The extract was dried at ambient temperature under a gentle stream of nitrogen. The residue was dissolved in 300 μl of mobile phase and 30 μl aliquot was injected via an automatic sampler into the liquid chromatograph and eluted with the mobile phase (10–9%, v/v methanol and acetonitrile, respectively in potassium dihydrogenphosphate buffer adjusted to pH 3.4) at a flow rate of 1 ml/min on a C 8 Symmetry cartridge column (5 μm, 150 mm×3.9 mm, Waters) at 25°C. The eluate was detected at 260 nm. Internal standard was 2-phenylimidazole. Sensitive and specific, this technique was performed to test urine of diabetic patients (smokers and non-smokers) admitted in an endocrinology service. Urinary cotinine seems to be a better marker of smoking status than thiocyanates.